Impact Du Changement Climatique Sur L’évolution De L'érosivité Des Pluies Dans Le Rif Occidental (Nord Du Maroc) - Choukri, Fatiha; Chikhaoui, Mohamed; Naimi, Mustapha; Raclot, Damien; Pepin, Yannick; Lafia, Kifayath (European Scientific Journal, ESJ, 2016)
The rainfall erosivity factor (R factor in Universal Soil Loss Equation), denoting rain energy, is a key factor for soil loss modeling. Its present and future estimation is thus significant for any action related to soil and water conservation and planning. The extended series of precipitations at high temporal resolution, essential to its evaluation, are not readily available in Morocco. The objective of this study is to predict the evolution of rainfall erosivity by 2080 in the Western Rif, based on predictions of daily rain provided by the General Climatic Models (GCMs). To reflect the seasonal variability of rainfall, and thus of R factor, a series of instantaneous rain measured over 35 consecutive years was used to monthly calibrate a model to calculate erosivity based of daily rainfall. The application of this model to the predictions of different GCMs and for various scenarios of climate evolution in Western Rif shows a weak evolution of erosivity on an annual timescale but a very strong evolution of the latter according to seasons with a reduction in R factor during winter and spring, and a pronounced increase during summer and autumn. This discernable change of the seasonality of rainfall erosivity is very useful for adjusting the evolution of agricultural practices and for selecting appropriate soil protection measures.